Social work practice with older people : a positive person-centred approach - Lynch, Rory, 4 0 16; 5 (Los Angeles, California : SAGE, 2014)
Older people are the biggest service user group for social workers and an increasing portion of the population. In this refreshingly positive and practical textbook, Rory Lynch draws on years of practice and teaching experience to show how to achieve best social work practice with older adults. He takes a person-centred approach, which fosters respect by valuing the fact that elderly people have more lived experience than others.Exploring the key theoretical approaches and methods of intervention, this book helps social workers to identify, understand and facilitate their service-users' wishes for wellbeing and a fulfilling older age. Chapters are practice-driven, containing case studies drawn from a range of care settings, reflective questions and exercises.Mapping directly onto the key modules on the social work degree, this is ...
Chapter 1. Historical context, law and policy -- chapter 2. Values and ethics -- chapter 3. Skills in working with older people -- chapter 4. Community care -- chapter 5. Mental health and well-being -- chapter 6. Dementia -- chapter 7. Assessment and intervention -- chapter 8. Gerontology -- chapter 9. Care settings for older people -- chapter 10. Being a research-practitioner.
Includes bibliographical references (pages [185]-206) and index.
Description based on MARC record for print version.
Keywords: 2 -- 0; 6; Social work with older people.;Social work with older people; 20; 2